Caracterização físico-química das principais variedades de mamão solo comercializadas na CEAGESP/SP - Ferraz, Rafael Augusto [UNESP]; Bardiviesso, Diógenes Martins [UNESP]; Leonel, Sarita [UNESP] (My University, 2012)
The papaya “Solo” presents a large market share of fruits in Brazil, with its preference mainly due to its small size and pleasant flavor. Currently a new variety of papaya has been prominent in the market, the variety “Benedict Smith”, which has won the consumer primarily for its appearance and flavor. Due to lack of information about this new cultivar, this study aimed to evaluate the physico-chemical characteristics of the main papaya “Solo” variety marketed in CEAGESP, in order to compare with the Benedito Soares variety. The study evaluated the physical characteristics of papaya fruits of Sunrise Solo cultivar, Golden cultivar and Benedito Soares cultivar with six replications of three fruits per experimental plot. The following characteristics were evaluated: mass, longitudinal diameter, equatorial diameter, cavity diameter, the pulp thickness, texture, color, the shape of internal cavity, soluble solids (SS), titratable acidity (AT), pH and relation SST/AT. The cultivar Benedict Soares had the highest longitudinal and equatorial diameter, a larger percentage of bark and pulp thickness, proving to be the largest fruit among the three cultivars. The cultivar Sunrise Solo had the lowest values of longitudinal diameter, smaller and larger percentage of bark and red pulp, whereas the Golden cultivar showed

O mamão ‘Solo’ apresenta uma grande participação no mercado de frutas do Brasil, sendo a sua preferência justificada principalmente pelo sabor agradável e pelo tamanho reduzido. Atualmente uma nova variedade de mamão têm se destacado no mercado, a cultivar denominada ‘Benedito Soares’, que tem conquistado o consumidor principalmente por sua aparência e sabor. Devido à falta de informações sobre esta nova cultivar, neste trabalho objetivou-se avaliar as características físico-químicas das principais variedades de mamão ‘Solo’ comercializadas no Entreposto terminal da CEAGESP/SP, com o intuito de compará-las com a ‘Benedito Soares’. No presente trabalho avaliou-se as características físicas dos frutos de mamoeiro das cultivares Sunrise Solo, Golden e Benedito Soares, sendo utilizadas 6 repetições e 3 frutos por parcela. Foram avaliadas as seguintes características: massa, diâmetro longitudinal, diâmetro equatorial, diâmetro da cavidade interna, espessura da polpa, textura, cor, formato da cavidade interna, sólidos solúveis (SS), acidez titulável (AT), pH e relação SS/AT. A cultivar Benedito Soares apresentou o maior diâmetro longitudinal e equatorial, maior porcentagem de casca e maior espessura de polpa, mostrando-se ser o maior fruto entre as três cultivares. A cultivar Sunrise Solo apresentou os menores valores de diâmetro longitudinal, menor porcentagem de casca e maior coloração vermelha da polpa. A cultivar Golden apresentou os maiores valores de textura, acidez titulável (AT), pH e menores valores de sólidos solúveis (SS) e ratio.
Physico-chemical characterization of the main varieties of papaya solo marketed in CEAGESP/SP
Keywords: Carica papaya L.; Benedict Soares cultivar; Sunrise solo; Golden; Quality; Carica papaya L.; Cultivar Benedito Soares; Sunrise solo; Golden; Qualidade